Objective: To determine social and sexual behaviors associated to sexually transmitted diseases (STD/HIV/AIDS) in youngsters from Alto Huallaga, Peru, in 2004. Design: Case-control study. Setting: Alto Huallaga’s health establishments. Participants: Young - Gómez, Walter (2008)
Objective: To determine social and sexual behaviors associated to sexually transmitted diseases (STD/HIV/AIDS) in youngsters from Alto Huallaga, Peru, in 2004. Design: Case-control study. Setting: Alto Huallaga’s health establishments. Participants: Youngsters 18 to 24 year-old. Interventions: Youngsters 18 to 24 year-old with STD/HIV/AIDS were studied. Bivariable statistics analysis consisted in chi–square test and Fisher’s test. Multivariable statistic analysis used logistic regression. For data prosecution and analysis we used STATA v9 and EPIDAT 3,1 statistic software. Main outcome measures: Age, family characteristics, sexual history and their association with STD/HIV/AIDS. Results: From 1518 subjects, 506 cases had sexually transmitted infection history and 1012 controls did not have STD antecedent; 921 (60,7%) were females, 29% came from Rupa Rupa, and 64% were 21 to 24 year-old. Both bivariate analysis and logistic regression analysis were associated to sex (female; OR 2,40 (95% CI 1,83 - 3,14)), age (21 to 24 years; OR 1,38 (95% CI 1,08 – 1,78)), types of friends (gang group; OR 1,19 (95% CI 1,05 - 1,35)), relationship between parents and children (do not talk to parents; OR 1,28 (95% CI 1,12 - 1,46)), age at sexual initiation (less than 14 year-old; OR 1,09 (95% CI 1,02 - 1,15)), number of sexual partners (two or more; OR 4,74 (95% CI 3,31 - 6,80)). Conclusions: The 21 to 24 years old group, gang group, parents and children that do not dialogue, first sexual relationship when less than 14 year-old, and having two or more sexual partners were the variables associated to sexually transmitted infections/ HIV/AIDS.